Advances in design and quality of melt electrowritten scaffolds - Kai Cao; Fucheng Zhang; Ahmadreza Zaeri; Yang Zhang; Ralf Zgeib; Mellina Calzolaio; Robert C. Chang (Materials & Design, 2023)
Melt electrowriting (MEW) is an emergent approach to fabricate 3D porous structured materials or scaffolds with microscale architectures. Due to its facile implementation, solvent-free process, and high tunability, functionalized MEW-enabled 3D structured materials are widely used to mimic the extracellular matrix, thereby providing a provisional structure for 3D tissue culture. This review firstly describes the state-of-art material design strategies that leverage the unique versatility of MEW to attribute 3D structured materials with tailored fiber diameter, macro-geometry, and micropattern, which is enabled by tuning different process parameters, customizing the collector shape, and designing the programmed toolpath, respectively. Secondly, advances in improving the quality of the MEW-enabled 3D structured materials, including the fiber uniformity and fiber placement accuracy, are comprehensively summarized. The common thread weaving through these advances is the observation that optimizing printing stability requires a synergistic tuning of various design and process parameters. To accomplish this, recent efforts have been made to quantify the fluctuation of the Taylor Cone, jet lag, and fiber diameter to clarify their correlations. The deterioration of fiber placement accuracy represented by the different fiber deviation modes is also systematically reviewed herein. Lastly, the unresolved challenges and prospective outlook in these aspects are also articulated.